Slab Waveguide and Optical Fibers for Novel Plasmonic Sensor Configurations - Cennamo, Nunzio (Sensors (Basel), 2017)
The use of plasmonic sensor devices often requires replaceable parts and disposable chips for easy, fast and on-site detection analysis. In light of these requests, we propose a novel low-cost surface plasmon resonance sensor platform for possible selective detection of analytes in aqueous solutions. It is based on a Polymethyl methacrylate (PMMA) slab waveguide with a thin gold film on the top surface inserted in a special holder, designed to produce the plasmonic resonance at the gold-dielectric interface. A wide-band light is launched in the PMMA slab waveguide through a trench realized in the holder directly, and illuminated with a PMMA plastic optical fiber (POF) to excite surface Plasmon waves. The output light is then collected by another PMMA POF kept at the end of the slab at an angle of 90° to the trench, and carried to a spectrometer. In this configuration, the trench has been used because a large incident angle is required for surface plasmon resonance excitation. The preliminary results showed that the sensor’s performances make it suitable for bio-chemical applications. The easy replacement of the chip allows for the production of an engineered platform by simplifying the measurement procedures.